PEMANFAATAN FRAMEWORK CODEIGNITER PADA APLIKASI PENGOLAHAN DATA PASIEN DI PUSKESMAS MAMAJANG - Patrick Richardo; Hamdan Arfandy; Arianti (KHARISMA Tech, 2021)
Mamajang Community Health Center is one of the public health service providers, which is located on Jalan Baji Minasa No.10 South Sulawesi. This Puskesmas serves 2 patient categories, namely general patients and corporate patients. General patients are residents or communities around the puskesmas while corporate patients are members of insurance companies that work with puskesmas. The Puskesmas mamajang provides 2 types of services, namely services for general practitioners and specialist doctors. The registration process for new patients is still done manually, namely by writing new patient data into a book called a patient visit list, then making a medical card and medical record card by writing it down on a piece of paper carried out by the Puskesmas administration officer This study aims to facilitate the performance of the Puskesmas in processing medical record data and patient data using the Codeigniter Framework. Creating a patient data management information system design at the Mamajang Community Health Center in order to help process patient data processing more effectively and efficiently. With the availability of databases that are processed in a structured information system, the puskesmas officers can complete tasks quickly, precisely and accurately and the data stored will be safer and also easier to process. Management can use the puskesmas information system as a method of reporting information so that it supports decision making for health service evaluation.